Pengaruh Pembelajaran Jarak Jauh Terhadap Kehidupan Sosial Siswa dan Prestasi Siswa Kelas 6 Di MIN 2 Kota Bandung - Dea Lita Salsabila, Restu Malihah Norma Yanti, Alvin Yanuar Rahman, (Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2021)
This study aims to determine the effect of the current covid-19 pandemic on distance learning in education. One of the most basic levels of formal education in Indonesia is the Islamic elementary school, Madrasah Ibtidaiyah. Policy updates due to the pandemic affect teaching and learning activities at this time. This research uses a descriptive qualitative research method. The learning used at Madrasah Ibtidaiyah Negeri 2 Bandung City in this study uses online learning that utilizes the power of the internet without being limited by distance, space and time so that learning during a pandemic continues. However, the existence of these influences both positively and negatively on social life and student achievement at this time. This is the importance of the role of parents and the method taught by the teacher even though the learning objectives are far from being fulfilled.